2020
DOI: 10.1038/s41562-020-00996-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving the precision of intranasal oxytocin research

Abstract: The neuropeptide oxytocin has been popularized for its role in social behaviour and nominated as a candidate treatment for several psychiatric illnesses.However, results so far have failed to reliably translate from animal models to human research. There have been justified calls to improve intranasal oxytocin delivery methodology, in terms of verifying that intranasal administration increases central levels of oxytocin. Nonetheless, improved methodology needs to be coupled with a robust theory of the role of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 170 publications
(169 reference statements)
0
48
0
Order By: Relevance
“…These results, which have been now extended to humans with intranasal oxytocin, indicate a role of this ancient neuropeptide in numerous features of human social interaction, from empathy (emotional and cognitive) and decision making to emotional face recognition, trust, and also in the alterations in social interaction seen in mental pathologies, such as in schizophrenia, autism, drug abuse, and addiction, as evidenced by the exponentially increasing number of studies that appear on these topics in scientific literature medlines (see [ 32 , 33 , 40 , 46 , 47 , 48 , 188 , 189 , 191 ] and references therein). Unfortunately, numerous criticisms have been raised on the enormous number of studies that have been produced, as so far, these studies have not been successfully translated for use in human research in healthy people and in patients affected by mental pathologies (see [ 38 , 39 ]) , making it difficult to trust this research on intranasal oxytocin in humans.…”
Section: Oxytocin Sexual Motivation and Sexual Arousalmentioning
confidence: 99%
See 2 more Smart Citations
“…These results, which have been now extended to humans with intranasal oxytocin, indicate a role of this ancient neuropeptide in numerous features of human social interaction, from empathy (emotional and cognitive) and decision making to emotional face recognition, trust, and also in the alterations in social interaction seen in mental pathologies, such as in schizophrenia, autism, drug abuse, and addiction, as evidenced by the exponentially increasing number of studies that appear on these topics in scientific literature medlines (see [ 32 , 33 , 40 , 46 , 47 , 48 , 188 , 189 , 191 ] and references therein). Unfortunately, numerous criticisms have been raised on the enormous number of studies that have been produced, as so far, these studies have not been successfully translated for use in human research in healthy people and in patients affected by mental pathologies (see [ 38 , 39 ]) , making it difficult to trust this research on intranasal oxytocin in humans.…”
Section: Oxytocin Sexual Motivation and Sexual Arousalmentioning
confidence: 99%
“…In conclusion, although studies in more naturalistic settings are necessary to confirm that oxytocin does not facilitate sexual behavior in men and women, the data available so far do not support a facilitatory role of oxytocin in human sexual behavior. As admitted by other researchers, the involvement of oxytocin in several components of human social interaction, from empathy (emotional and cognitive) to trust and even in the alteration of these aspects found in mental pathologies (from schizophrenia, autism, and depression to drug abuse and addiction) remains elusive and difficult to reproduce [ 27 , 28 , 38 , 39 ]. The lack of reproducible study results is a very important problem, as this makes it impossible to confirm that a given effect that has been reported is truly due to oxytocin treatment.…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…While our knowledge concerning the neuroanatomical and functional connectivity of the hypothalamic oxytocinergic neurons within the brain has increased significantly since the development of virus-based opto- and chemo-genetic physiological approaches [ 6 , 40 , 48 ], much more is known about the distribution of the OXTR in the brain. This knowledge is critical in constructing and testing theories relating to the effects of endogenous and exogenous oxytocin on appetite regulation and metabolism [ 49 ]. Oxytocin acts via a single oxytocin receptor which belongs to the seven-transmembrane G-protein-coupled receptor family and is coupled to phospholipase C through Gαq11 [ 50 ].…”
Section: The Distribution Of the Oxytocin Receptor In The Brain—further Evidence Linking Oxytocin And Appetite Regulationmentioning
confidence: 99%
“…Only 1–2% of peripherally synthesized oxytocin penetrates the blood-brain barrier [ 212 ] and an even smaller proportion of subcutaneously/intravenously administrated oxytocin reaches the CSF [ 140 ]. A recent study has shown that labeled IN oxytocin given to rhesus macaques was later detected in brain regions that lie in the trajectories of the olfactory and trigeminal nerves, suggesting that IN oxytocin delivery into the CNS bypasses the blood-brain barrier [ 49 , 213 ]. Studies in humans [ 214 ], non-human primates [ 215 , 216 ], and rodents [ 217 , 218 ] have shown subsequent increase in oxytocin in the CSF 60–75 min [ 214 , 216 ] following IN oxytocin application.…”
Section: Interventional Studies Of Oxytocin Administration In Humansmentioning
confidence: 99%